The Role of Dividend Policy in Inventing the Effect of Accounting Profit, Cash Flow, Operation and Corporate Size on the Price of Closing Stock - Murtiadi Awaluddin; Febriani Setijawan; Rulyanti Susi Wardhani; Muh. Akil Rahman (Basic and Applied Accounting Research Journal, 2021)
This study aims to determine the effect of accounting profit, operating cash flow and company size on the closing price of shares through dividend policy on consumer goods industry companies on the Indonesia Stock Exchange. This research uses quantitative methods and types of explanatory research, with 2016-2018 observation years in 17 company samples. The results showed (1) Accounting profit and operating cash flow had a positive and significant effect on dividend policy, while the size of the company had no influence on dividend policy. (2) Accounting profit and operating cash flow have no effect on the closing price of shares, while the size of the company has a positive and significant effect on the closing price of shares. (3) Dividend policy has a positive and significant effect on the closing price of shares. (4) There is no indirect effect of dividend policy in mediating accounting profit and operating cash flow on the closing price of shares, but there is an indirect effect of dividend policy in mediating company size on the closing price of shares